Microstructure evolution and interfacial reaction of TiAl–Si alloy solidified in alumina crucible. (14th November 2015) - Fan, J.; Guo, J.; Wang, S.; Tian, S.; Su, Y.; Liu, J.; Fu, H.
Abstract : The microstructure evolution of Ti–43Al–3Si (at-%) alloy solidified in alumina crucible was investigated by directional solidification technology. After directional solidification, the microstructure of the alloy is consisted of γ-TiAl, α2 -Ti3 Al, ξ-Ti5 Si3 phases and Al2 O3 particles. There are three morphologies of ξ phases formed in the alloy, namely, long rod-like, cluster-like with eutectic morphology, and needle-like shape. The volume fraction of ξ phases decreases with increasing growth rates. Al2 O3 particles broke from the crucible and enter into the melt by the thermal physical erosion. Al2 O3 particles enrich in the liquid phase with the moving of solid-liquid interface, and are captured or entrapped by dendrites during solidification. The Al2 O3 particles mainly distributed in the interdendritic region, and some particles exist in dendrites.